Pendampingan Pemanfaatan Media Pembelajaran Interaktif di SD Negeri Inpres Koya Tengah Kecamatan Muara Tami Kota Jayapura - Tiffany Shahnaz Rusli; Aisyah Ali; Wasito (Universitas Cenderawasih, 2023)
Interactive learning media has great potential in improving the quality of education in Indonesia, especially in elementary schools. This article discusses the results of PKM research which aims to provide assistance in the use of interactive learning media at SD Negeri Inpres Koya Tengah, Muara Tami District, Jayapura City. This research aims to improve the effectiveness of learning at the school. The method of implementing activities consists of a preparation stage, an implementation stage. The results of the activity show that the assistance and use of interactive learning media at SD Negeri Inpres Koya Tengah has had a positive impact on the learning process.